Evaluation. - Green, Jackie (McGraw-Hill International (UK) Ltd., 2006)
What is evaluation? This work provides an examination of the key theories and principles underpinning approaches to evaluation. It offers a guide to how these principles can be implemented in practice and provides insights into dealing with some of the real-life challenges and complexities of evaluation.